2018
DOI: 10.22159/ijap.2017.v9s2.20
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Effect of Virgin Coconut Oil on the Viability of Chromogenic Bacteria That Causes Dental Black Stain in Children

Abstract: Introduction: Virgin coconut oil (VCO) is a natural antibacterial agent with the ability to kill microorganisms whose cell membranes contain lipids, including Gram-positive and Gram-negative bacteria, such as Actinomyces sp. and Prevotella spp. No study on the antibacterial effects of VCO on the chromogenic bacteria that causes dental black stains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
4
1
1
Order By: Relevance
“…VCO has antimicrobial activity against Candida albicans, Staphylococcus aureus, Streptococcus mutans, Actinomyces spp., Prevotella spp. and Cytomegalovirus [8,18,19]. In this study, the optical density value of VCO mousse 80% showed no statistically significant difference compared to the negative control.…”
Section: Discussioncontrasting
confidence: 47%
“…VCO has antimicrobial activity against Candida albicans, Staphylococcus aureus, Streptococcus mutans, Actinomyces spp., Prevotella spp. and Cytomegalovirus [8,18,19]. In this study, the optical density value of VCO mousse 80% showed no statistically significant difference compared to the negative control.…”
Section: Discussioncontrasting
confidence: 47%
“…Also, the presence of lauric acid inhibited the growth of Staphylococcus aureus, Bacillus cereus, Salmonella typhimurium, and Escherichia coli. Gayatri et al [ 21 ] proposed an in vitro experiment that tested the antibacterial effects of VCO on the bacterial viability of Actinomyces and Prevotella species that caused tooth discoloration in children, and it was concluded that 100% VCO significantly reduced the viability of Prevotella species. This outcome supported the efficiency of 100% VCO employed in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, patients meeting the diagnostic criteria were considered "cases, " whereas those who do not were considered "controls" or "comparators. " However, since the tendency of BS to recur is a well-documented phenomenon [5], children who might have received recent treatment for BS, could have been easily misplaced into control groups, as none of the studies reported inquiring about the past history of BS presence. It should be noted that a biased detection of the participants' status constitutes as bias, could possibly influence the study results [39].…”
Section: Discussionmentioning
confidence: 99%
“…It affects both adults and children but is more commonly seen in children [3]. Despite not being associated with any functional impairment, it has constantly been regarded as a source of esthetic concern for children and their families [4], all the more because of its high recurrence tendency [5].…”
Section: Introductionmentioning
confidence: 99%